Attenuated brain activity during error processing and punishment anticipation in procrastination – a monetary Go/No-go fMRI study - Wypych, Marek; Michałowski, Jarosław M.; Droździel, Dawid; Borczykowska, Magda; Szczepanik, Michał; Marchewka, Artur (Scientific reports, 2019)
Procrastination is a self-regulatory failure in which people voluntarily but irrationally delay important tasks. Trait procrastination is estimated to affect 15–20% of the total population and leads to a significant decrease in performance, satisfaction with achievements, and quality of life. Procrastination is related to impulsivity and reduced executive control, especially in the domain of inhibition. Moreover, procrastinatory tendencies seem to increase with negative affect, suggesting impaired emotion regulation. The aim of this study was to investigate the neuronal mechanisms of inhibition, error processing, and behavioral control under pressure of punishment in procrastinators. Non-student subjects recruited to low (LP) and high procrastination (HP) groups performed an fMRI monetary Go/No-go task. HP showed significantly lower error-related activity in ACC than LP. There was also a significant group by condition interaction in the ACC and right DLPFC suggesting increase of control during the punishment condition in LP but not HP group. These results suggest that procrastinators have impaired error processing mechanisms which may add to the persistence of procrastination through difficulties in correction of faulty behaviors. Procrastination also seems to be related to a decreased ability to intensify self-control in more demanding situations and/or impaired coping in the context of negative situations.